Depressive symptoms and its influencing factors of older people with cataracts in China: a national cross-sectional survey - Niu, Tengfei; Cao, Shiwei; Wang, Xiaoyu; Xian, Xiaobing; Luo, Chunyang; Ma, Jingxi (Frontiers in Public Health, 2025)
BackgroundDepressive symptoms are a common complication in patients with cataracts and may exacerbate cataract symptoms. Therefore, it is important to focus on depressive symptoms and their influencing factors in older people with cataracts. The purpose of this study was to investigate the prevalence rate of depressive symptoms and influencing factors in Chinese older people with cataracts.MethodsDescriptive analyses were used to report the sociodemographic characteristics, lifestyle, health status, and depressive symptoms of old people with cataracts in China. The chi-square test was used to compare differences between subjects with different demographic characteristics. Binary logistic regression was used to analyze the factors that influenced the depressive symptoms of cataract patients. Meanwhile, a random forest model was developed in this study to rank the importance of the influencing factors.ResultsThree hundred and six (25.27%) of 1,211 cataract patients included in this study suffered from depressive symptoms. Logistic regression analysis suggested that poor economic situation (AOR = 3.162, 95%CI: 1.719–5.817), social participation (AOR = 1.530, 95%CI: 1.053–2.222), having hearing disorder (AOR = 1.445, 95%CI: 1.040–2.008), poor self-reported health status (AOR = 2.646, 95%CI: 1.705–4.106), poor life satisfaction (AOR = 3.586, 95%CI: 1.652–7.784) were risk factors for depressive symptoms in cataract patients and consumption of fresh fruits (AOR = 0.587, 95%CI: 0.369–0.933) was a protective factor for depressive symptoms in cataract patients. The results of the random forest showed that self-reported health status was the most important factor influencing depressive symptoms in cataract patients. The other factors, in order of importance, were life satisfaction, economic situation, fruits, hearing disorder, and social participation.ConclusionThe results suggested that the development of depressive symptoms in cataract patients was influenced by various factors. Medical staff should monitor these influencing factors more closely when treating and caring for patients with cataracts.